Fate of Methane Released From a Destroyed Oil Platform in the Gulf of Mexico - Silva, Mauricio; Roa, Camilo; Ali, Nizar Bel Haj; O’Reilly, Carrie; Abichou, Tarek; MacDonald, Ian R. (Frontiers in Earth Science, 2022)
In 2004, destruction of a Gulf of Mexico oil platform by Hurricane Ivan initiated a discharge of oil and gas from a water depth of 135 m, where its bundle of well conductors was broken below the seafloor near the toppled wreckage. Discharge continued largely unabated until 2019, when findings partly reported herein prompted installation of a containment device that could trap oil before it entered the water column. In 2018, prior to containment, oil and gas bubbles formed plumes that rose to the surface, which were quantified by acoustic survey, visual inspection, and discrete collections in the water column. Continuous air sampling with a cavity ring-down spectrometer (CRDS) over the release site detected atmospheric methane concentrations as high as 11.7, ~6 times greater than an ambient baseline of 1.95 ppmv. An inverse plume model, calibrated to tracer-gas release, estimated emission to the atmosphere of 9 g / s. In 2021, the containment system allowed gas to escape into the water at 120 m depth after passing through a separator that diverted oil into storage tanks. The CRDS detected transient peaks of methane as high as 15.9 ppmv ppm while oil was being recovered to a ship from underwater storage tanks. Atmospheric methane concentrations were elevated 1-2 ppmv over baseline when ship was stationary within surfacing plumes of gas after oil was removed from the flow. Oil rising to the surface was a greater source of methane to the atmosphere than associated gas bubbles.